Feasibility of Reduced Lap-Spliced Length in Polyethylene Fiber-Reinforced Strain-Hardening Cementitious Composite - Wonchang Choi; Seok-Joon Jang; Hyun-Do Yun (Advances in Materials Science and Engineering)
This research investigates the interfacial behavior between polyethylene (PE) fiber-reinforced strain-hardening cement composite (PE-SHCC) and reinforcing bars that are spliced in the tension region to determine feasibility of reduced lap-spliced length in PE-SHCC. Twenty test specimens were subjected to monotonic and cyclic tension loads. The variables include the replacement levels of an expansive admixture (0% and 10%), the compressive strength of the SHCC mixtures (40 MPa and 80 MPa), and the lap-spliced length in the tension region (40% and 60% of the splice length recommended by ACI 318). The PE-SHCC mixture contains polyethylene fiber to enhance the tensile strength, control the widths of the cracks, and increase the bond strength of the lap splice reinforcement and the calcium sulfo-aluminate- (CSA-) based expansive admixture to improve the tension-related performance in the lap splice zone. The results have led to the conclusion that SHCC mixtures can be used effectively to reduce the development length of lap splice reinforcement up to 60% of the splice length that is recommended by ACI 318. The addition of the calcium sulfo-aluminate-based expansive admixture in the SHCC mixtures improved the initial performance and mitigated the cracking behavior in the lap splice region.